Islam and the Prevention of Violence Against Children Through the Implementation of the National Movement Against Sexual Crimes - Naila Farah; Lutfiana Nisarohmah; Ratri Wulandari; Tryana Hafilda Dewi (Parahyangan Catholic University, 2022)
Today, many cases of violence are widely reported in the mass media. The most recent case is the problem of sexual violence that affects children, where most of the perpetrators are acquaintances of the victim. Children become targets of violence because their position is always judged as weak, helpless, and dependent on the adults around them. This study discusses the state and religion's role in protecting children from sexual violence. This research was conducted with a sociological approach through the resource mobilization theory. The results of this study inform the definition of violence, Islamic views on children, and efforts to protect children through the National Movement Against Sexual Crimes Against Children (Gerakan Nasional Anti Kejahatan Seksual Terhadap Anak; GN-AKSA). The conclusion of this study shows that Islamic values ​​that advocate for good care of children can be merged with GN-AKSA as an effort to protect children from sexual violence.